Assessment of the Environmental Consequences Caused by Endogenous and Anthropogenic Hazards for the Azov Recreation Area - PAVLOVA, Alla; ZARETSKAYA, Marina; TELYATNIKOV, Ilya; RUBTSOV, Sergey (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.v10.7(39).02, 2020)
The Russian sector of the Azov recreational area is under the influence of numerous pollution sources of anthropogenic or natural origin. To ensure a comfortable recreation and recovery of the population, it is necessary to apply methods of integrated system monitoring, which makes it possible to identify patterns of the pollution formation in heterogeneous areas of the territory and places of increased environmental risk. Mathematical and simulation modelling should be an integral part of such systems, as a tool for scenario analysis, forecasting and warning. The paper proposes cellular automaton modelling methods, which have the advantages of expressivity, which allows for expansion of the possibilities for studying complex physicochemical processes and phenomena associated with the migration and transformation of reagents in the atmosphere and in the aquatic environment. The method is implemented in the form of a software application. We also present the results of the simulation of diffusion process and two substances - products of combustion in a fire with a point localization of epicentres; independent dispersion and interaction of light fractions of emission products upon activation of a land volcano and heavy fractions of mud volcano breccias of an underwater mud volcano.